Method for preparing excited admixture from circulating fluidized bed ash

By detecting the activated alumina and sulfur trioxide content in the raw materials, scientifically evaluate the amount of excitant added, and a predictable circulating fluidized bed ash slag excited blend was prepared, which solved the problem of lack of predictability in the assessment of the appropriateness of excitant addition amount in the prior art, and achieved long-term performance prediction and resource utilization improvement of the excited blend.

CN119638284APending Publication Date: 2025-03-18EAST CHINA UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803171.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art cannot effectively predict the long-term performance of circulating fluidized bed ash slag excited blends, especially lacking in the assessment of the suitability of the excitant amount.

Method used

By detecting the mass percentage content of activated alumina and sulfur trioxide in the raw materials, combining the reaction requirements of activated alumina and sulfate, scientifically evaluate the amount of excitant addition, and quantitative and predictive excited blends were prepared.

Benefits of technology

The long-term performance prediction of the excited state blend of circulating fluidized bed ash slag is achieved, the utilization rate of CFB ash slag is improved, and the demand for natural resources is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for preparing an excited admixture from circulating fluidized bed ash, and belongs to the field of waste resourceful treatment. The method comprises the following steps: respectively detecting the raw materials to obtain the mass percentage contents of activated aluminum oxide and sulfur trioxide in the raw materials; the raw materials comprise circulating fluidized bed ash, cement, a conditioning agent and an exciting agent; the raw materials and the retarder are mixed to obtain the excited admixture. In the invention, the cement and the exciting agent can excite the CFB ash to form more chemical active substances and provide stable physical strength, the hardening and tempering agent can further improve the application performance of the excited admixture, and the retarder can change the setting time of the excited admixture. According to the method, the raw materials are detected respectively, the mass percentage content of the activated aluminum oxide and the mass percentage content of the sulfur trioxide in the raw materials are obtained, the adding amount of the exciting agent is evaluated according to the reaction requirement of the activated aluminum oxide and the sulfate, quantification and scientization are achieved, and meanwhile anticipation is achieved, especially long-term performance anticipation is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste resource treatment, and in particular to a method for preparing excited state admixtures from circulating fluidized bed ash. Background Art

[0002] The treatment and disposal of circulating fluidized bed (CFB) ash has become a huge bottleneck in the development of CFB boiler thermal power plants. Relevant research experience shows that the coordinated utilization of solid waste is an effective way to convert solid waste into resources.

[0003] The related technology does not distinguish between active and inactive alumina for CFB ash, and requires performance testing of the prepared excited admixtures to judge whether the activator effect and the amount of activator added in the short term are appropriate. It does not have predictive value, especially for long-term performance. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for preparing excited state admixtures from circulating fluidized bed ash. The present invention evaluates the amount of activator to be added based on the reaction requirements of activated alumina and sulfate, which is quantitative and scientific, and has predictive properties, especially long-term performance predictive properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing excited state admixture from circulating fluidized bed ash, comprising the following steps:

[0007] The raw materials are tested respectively to obtain the mass percentage of activated alumina (AAl) and sulfur trioxide (S) in each raw material; the raw materials include circulating fluidized bed ash, cement, a conditioning agent and an activator; the activated alumina refers to an alumina component that can completely react with sufficient calcium oxide at 100° C. within 3 hours, and is not the alumina component referred to in traditional material chemical composition testing;

[0008] The raw materials and the retarder are mixed to obtain the excited state admixture.

[0009] Preferably, the conditioning agent includes one or more of anhydrite, hemihydrate gypsum and dihydrate gypsum.

[0010] Preferably, the amount of the conditioning agent added is controlled by Formula I:

[0011] (M1×AAl CFB灰渣 +M2×AAl 激发剂 +M3×AAl 水泥 )×0.0098 / (0.0125S)>0.5 Formula I,

[0012] In Formula I, AAlCFB灰渣 AAl is the mass percentage of activated alumina in circulating fluidized bed ash; 激发剂 AAl is the mass percentage of activated alumina in the activator; 水泥 is the mass percentage of activated alumina in cement, M1 is the mass percentage of circulating fluidized bed ash in excited admixture, M2 is the mass percentage of activator in excited admixture, M3 is the mass percentage of cement in excited admixture, and S is the mass percentage of total sulfur trioxide of circulating fluidized bed ash, cement, tempering agent and activator in excited admixture.

[0013] Preferably, the total sulfur trioxide content in the excited state admixture is ≤7wt%.

[0014] Preferably, the activator is a substance containing activated alumina.

[0015] Preferably, the activator comprises dye sludge containing activated alumina and / or sludge from aluminum-containing wastewater.

[0016] Preferably, the mass percentage of the retarder in the excited state admixture is 0.01% to 0.5%.

[0017] Preferably, the retarder includes an organic retarder and / or an inorganic retarder; the organic retarder includes one or more of carbohydrate compounds, carboxylic acids, carboxylates, polycarboxylates, lignin sulfonates, polyols and polyol derivatives; the inorganic retarder includes one or more of boric acid, borates, fluorine-containing silicates, zinc salts, barium salts and zinc oxide.

[0018] Preferably, the retarder also includes a water reducing agent.

[0019] Preferably, the fluidity of the excited state admixture is 180±5 mm.

[0020] The present invention provides a method for preparing an excited state admixture from circulating fluidized bed ash, comprising the following steps: testing the raw materials respectively to obtain the mass percentage of activated alumina and sulfur trioxide in each raw material; the raw materials include circulating fluidized bed ash, cement, a conditioning agent and an activator; the activated alumina refers to an alumina component that can completely react with sufficient calcium oxide at 100°C within 3 hours, and is not the alumina component referred to in traditional material chemical composition testing; the raw materials and a retarder are mixed to obtain the excited state admixture.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] In the present invention, cement and activator can activate CFB ash to form more chemically active substances, provide stable physical strength, the conditioning agent can further improve the application performance of the excited state admixture, and the retarder can change the setting time of the excited state admixture. The present invention detects the raw materials respectively, obtains the mass percentage of activated alumina and sulfur trioxide in each raw material, and evaluates the addition amount of the activator according to the reaction requirements of activated alumina and sulfate, which is quantitative and scientific, and has predictive properties, especially long-term performance predictive properties, which can improve the utilization rate of CFB ash and reduce the demand for natural resources.

[0023] Furthermore, the present invention defines that the amount of the tempering agent added is controlled by Formula I, which can enhance the combined effect of CFB ash, activator and tempering agent to form two synergistic effects: ① the synergistic effect of the activator and CFB ash, using the active alumina in the activator to react with the alkali, alkali-soluble silicon and alkali-soluble aluminum in the CFB ash to form silicates and aluminosilicates, thereby increasing the chemical reaction degree of the excited admixture and thus improving the strength; ② the synergistic effect between gypsum sulfate and aluminosilicates and aluminates, using the tempering agent to react with aluminosilicates and aluminates to form one or more substances of ettringite (AFt) and low-sulfur sulfoaluminate (AFm), thereby increasing the density in the excited admixture without causing strength shrinkage. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing excited state admixture from circulating fluidized bed ash, comprising the following steps:

[0025] The raw materials are tested respectively to obtain the mass percentage of activated alumina and sulfur trioxide in each raw material; the raw materials include circulating fluidized bed ash, cement, conditioning agent and activator; the activated alumina refers to the alumina component that can completely react with sufficient calcium oxide at 100°C within 3 hours, and is not the alumina component referred to in traditional material chemical composition testing;

[0026] The raw materials and the retarder are mixed to obtain the excited state admixture.

[0027] The present invention detects the raw materials respectively to obtain the mass percentage of activated alumina and sulfur trioxide in each raw material; the raw materials include circulating fluidized bed ash, cement, a conditioning agent and an activator; the activated alumina refers to an alumina component that can completely react with sufficient calcium oxide at 100°C within 3 hours, and is not the alumina component referred to in traditional material chemical composition detection.

[0028] In the present invention, the method for detecting the mass percentage of sulfur trioxide is preferably carried out according to GB / T1596; the method for detecting the mass percentage of activated alumina is preferably carried out according to T / CBMF90.

[0029] The present invention has no particular limitation on the source of the circulating fluidized bed ash.

[0030] In the present invention, the conditioning agent preferably includes one or more of anhydrite, hemihydrate gypsum and dihydrate gypsum.

[0031] In the present invention, the amount of the conditioning agent added is preferably controlled by Formula I:

[0032] (M1×AAl CFB灰渣 +M2×AAl 激发剂 +M3×AAl 水泥 )×0.0098 / (0.0125S)>0.5 Formula I,

[0033] In Formula I, AAl CFB灰渣 AAl is the mass percentage of activated alumina in circulating fluidized bed ash, in %; 激发剂 The mass percentage of activated alumina in the activator, in %; AAl 水泥 is the mass percentage of activated alumina in cement, in %, M1 is the mass percentage of circulating fluidized bed ash in excited state admixture, in %, M2 is the mass percentage of activator in excited state admixture, in %, M3 is the mass percentage of cement in excited state admixture, in %, and S is the mass percentage of total sulfur trioxide of circulating fluidized bed ash, cement, tempering agent and activator in excited state admixture, in %. The present invention defines that the amount of the tempering agent added is controlled by formula I, which can enhance the combined effect of CFB ash, activator and tempering agent, and form two synergistic effects: ① the synergistic effect of the activator and CFB ash, using the active alumina in the activator to react with the alkali, alkali-soluble silicon and alkali-soluble aluminum in the CFB ash to form silicates and aluminosilicates, thereby increasing the chemical reaction degree of the excited admixture and thus improving the strength; ② the synergistic effect between gypsum sulfate and aluminosilicates and aluminates, using the tempering agent to react with aluminosilicates and aluminates to form one or more substances of ettringite (AFt) and low-sulfur sulfoaluminate (AFm), thereby increasing the density in the excited admixture.

[0034] In the present invention, the M1 is preferably 40% to 75%, specifically 40%, 50%, 60%, 71% or 75%; the M2 is preferably 4% to 20%, specifically 4.7%, 10%, 15% or 20%; the M3 is preferably 10% to 40%, specifically 10%, 19%, 30% or 40%, and exceeding 40% will increase the cost.

[0035] In the present invention, the total sulfur trioxide content in the excited state admixture is preferably ≤7wt%, specifically 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6.6wt% or 7wt%.

[0036] In the present invention, the activator is preferably a substance containing activated alumina.

[0037] In the present invention, the activator preferably includes dye sludge containing activated alumina and / or sludge from aluminum-containing wastewater. The present invention has no particular limitation on the specific source of the activator, and any source known to those skilled in the art can be used.

[0038] In the present invention, the mass percentage of the retarder in the excited state admixture is preferably 0.01% to 0.5%, specifically 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. Exceeding 0.5% will increase the cost.

[0039] In the present invention, the retarder preferably includes an organic retarder and / or an inorganic retarder; the organic retarder preferably includes one or more of a carbohydrate compound, a carboxylic acid, a carboxylate, a polycarboxylic acid, a lignin sulfonate, a polyol and a polyol derivative, the carbohydrate compound preferably includes sucrose, the carboxylate preferably includes sodium gluconate, and the carboxylic acid preferably includes tartaric acid and citric acid; the inorganic retarder preferably includes one or more of boric acid, a borate, a fluorine-containing silicate, a zinc salt, a barium salt and zinc oxide, the borate preferably includes borax, the fluorine-containing silicate preferably includes sodium fluorosilicate, the zinc salt preferably includes zinc chloride, and the barium salt preferably includes barium chloride.

[0040] In the present invention, the retarder preferably also includes a water reducer, and the water reducer is preferably a polycarboxylic acid water reducer.

[0041] In the present invention, the cement is preferably general-purpose Portland cement, more preferably Portland PO 42.5 cement.

[0042] In the present invention, the fluidity of the excited state admixture is preferably 180±5 mm, specifically 175, 180 or 185 mm.

[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The mass percentage content of sulfur trioxide in the examples and comparative examples of the present invention is determined according to GB / T1596; the mass percentage content of activated alumina is determined according to T / CBMF90.

[0045] Example 1

[0046] The mass percentages of activated alumina in CFB ash, dye sludge and cement (general silicate PO 42.5 cement) are 8.61%, 17.80% and 8.28% respectively. The mass percentages of sulfur trioxide in CFB ash, dye sludge and cement are 5.89%, 1.19% and 1.47% respectively.

[0047] The designed mass percentages are 71.0% CFB ash, 4.7% dye sludge, 19.0% general silicate P.O42.5 cement, and 5.3% dihydrate gypsum with a purity of 100wt% is added, which is calculated by formula I (71×8.61+4.7×17.80+19×8.28)×0.0098 / (0.0125×(71×5.89+4.7×1.19+19×1.47+5.3×46.47)) to be 0.96. The mass percentage of total sulfur trioxide in the excited state admixture is calculated to be 7.0%. After adding citric acid retarder (the mass percentage of citric acid in the excited state admixture is 0.1%), the fluidity of the excited state admixture is 180mm. According to GB / T 17671, the 7d compressive strength is 18.2MPa, the flexural strength is 4.7MPa, the 28d compressive strength is 23.3MPa, the flexural strength is 5.8MPa. According to GB / T1346, the initial setting time is 365min, and the final setting time is 700min.

[0048] Example 2

[0049] The mass percentages of activated alumina in CFB ash, dye sludge and general silicate PO 42.5 cement are 3.93%, 2.20% and 8.28% respectively. The mass percentages of sulfur trioxide in CFB ash, dye sludge and cement are 6.92%, 1.01% and 1.47% respectively.

[0050] The designed mass percentages are 62.4% CFB ash, 14.4% dye sludge, 19.2% general silicate P.O42.5 cement, and 4.0% of dihydrate gypsum with a purity of 100wt%. According to formula I, (62.4×3.93+14.4×2.20+19.2×8.28)×0.0098 / (0.0125×(62.4×6.92+14.4×1.01+19.2×1.47+4×46.47)) is 0.52. The mass percentage of total sulfur trioxide in the excited state admixture is calculated to be 6.6%. After adding barium chloride retarder (the mass percentage of barium chloride in the excited state admixture is 0.5%), the fluidity of the excited state admixture is 185mm. According to GB / T 17671, the 7d compressive strength is 20.8MPa, the flexural strength is 4.6MPa, the 28d compressive strength is 28.2MPa, the flexural strength is 6.2MPa. According to GB / T1346, the initial setting time is 412min, and the final setting time is 688min.

[0051] Example 3

[0052] The mass percentages of activated alumina in CFB ash, dye sludge and general silicate PO 42.5 cement are 8.61%, 17.80% and 8.28% respectively. The mass percentages of sulfur trioxide in CFB ash, dye sludge and cement are 5.89%, 1.19% and 1.47% respectively.

[0053] The designed mass percentages are 51.7% CFB ash, 10% dye sludge, 37.8% general silicate P.O42.5 cement, and 0.5% of dihydrate gypsum with a purity of 100wt%. According to formula I, (51.7×8.61+10×17.80+37.8×8.28)×0.0098 / (0.0125×(51.7×5.89+10×1.19+37.8×1.47+0.5×46.47)) is 1.86. The mass percentage of total sulfur trioxide in the excited state admixture is calculated to be 4.0%. After adding citric acid and sodium fluorosilicate retarders (the mass percentage of citric acid in the excited state admixture is 0.1%, and the mass percentage of sodium fluorosilicate is 0.2%), the fluidity of the excited state admixture is 175mm. According to GB / T 17671, the 7d compressive strength is 24.2MPa, the flexural strength is 5.6MPa, the 28d compressive strength is 35.7MPa, and the flexural strength is 7.0MPa. According to GB / T1346, the initial setting time is 480min, and the final setting time is 708min.

[0054] Example 4

[0055] The mass percentages of activated alumina in CFB ash, dye sludge and general silicate PO 42.5 cement are 8.61%, 17.80% and 8.28% respectively. The mass percentages of sulfur trioxide in CFB ash, dye sludge and cement are 5.89%, 1.19% and 1.47% respectively.

[0056] The designed mass percentages are 51.7% CFB ash, 10% dye sludge, 37.8% general silicate P.O42.5 cement, and 0.5% of dihydrate gypsum with a purity of 100wt%. According to formula I, (51.7×8.61+10×17.80+37.8×8.28)×0.0098 / (0.0125×(51.7×5.89+10×1.19+37.8×1.47+0.5×46.47)) is 1.86. The mass percentage of total sulfur trioxide in the excited state admixture is calculated to be 4.0%. After adding citric acid and sodium fluorosilicate retarders (the mass percentage of citric acid in the excited state admixture is 0.1%, and the mass percentage of sodium fluorosilicate is 0.2%), the amount of water added to the excited state admixture is changed to control the fluidity to 160mm. According to GB / T 17671, the 7d compressive strength is 24.7MPa, and the flexural strength is 5.2MPa. The 28d compressive strength is 26.05MPa, and the flexural strength is 4.2MPa. According to GB / T1346, the initial setting time is 216min, and the final setting time is 288min.

[0057] Comparative Example 1

[0058] The mass percentages of activated alumina in CFB ash, dye sludge and general silicate PO 42.5 cement are 3.93%, 2.20% and 8.28% respectively. The mass percentages of sulfur trioxide in CFB ash, dye sludge and cement are 6.92%, 1.01% and 1.47% respectively.

[0059] The designed mass percentages are 70% CFB ash, 0% dye sludge, 24% general silicate P.O42.5 cement, and 6.0% of dihydrate gypsum with a purity of 100wt%. According to formula I, (70×3.93+0×2.20+24×8.28)×0.0098 / (0.0125×(70×6.92+0×1.01+24×1.47+6×46.47)) is 0.47. The mass percentage of total sulfur trioxide in the excited state admixture is calculated to be 8.0%. After adding barium chloride retarder (the mass percentage of barium chloride in the excited admixture is 0.5%), the 7d compressive strength is 14.6MPa and the flexural strength is 4.2MPa according to GB / T 17671, the 28d compressive strength is 18.7MPa and the flexural strength is 4.5MPa. According to GB / T1346, the initial setting time is 367min and the final setting time is 420min.

[0060] Comparative Example 2

[0061] The CFB ash and cement in Example 2 were selected, and water glass (modulus 2.4) and sodium carbonate were selected as activators.

[0062] The dosage of water glass is 5wt%, the dosage of sodium carbonate is 2wt%, and according to the ratio of CFB ash and general silicate PO 42.5 cement in Example 2, the dosage is designed to be 71.12% CFB ash and 21.88% general silicate PO42.5 cement. After adding barium chloride retarder (the mass percentage of barium chloride in the excited admixture is 0.5%), according to GB / T17671, the 7d compressive strength is 16.1MPa, the flexural strength is 4.8MPa, the 28d compressive strength is 14.3MPa, the flexural strength is 3.2MPa, according to GB / T1346, the initial setting time is 72min, and the final setting time is 127min.

[0063] It can be seen from Example 1 and Comparative Example 1 that the method provided by the present invention can effectively improve the flexural strength and compressive strength of the excited admixture sample, and effectively extend the setting time, especially the final setting time.

[0064] It can be seen from Example 2 and Comparative Example 2 that the method provided by the present invention can effectively improve the flexural strength and compressive strength of the excited state admixture sample, and there will be no strength shrinkage phenomenon. The reason why the strength shrinkage occurred in Comparative Example 2 is that the reaction degree and reaction amount were not scientifically controlled according to the reaction requirements of activated alumina and sulfate, so that more AFt was formed after 28 days, which led to the expansion of the sample volume and the strength shrinkage phenomenon. In addition, Comparative Example 2 was also unable to effectively control the setting time.

[0065] It can be seen from Examples 3 and 4 that the method provided by the present invention can effectively improve the late (28 days) flexural strength and compressive strength of the excited state admixture sample and effectively control the setting time. Example 4 Due to the low fluidity, the apparent porosity is high during the slurry casting process. The low fluidity also leads to uneven growth of AFt and expansion stress. All these factors lead to a shortened setting time of the sample, cracking in the late stage, and reduced strength.

[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing excited state admixture from circulating fluidized bed ash, characterized in that: The following steps are involved: The raw materials are tested respectively to obtain the mass percentage of activated alumina and sulfur trioxide in each raw material; the raw materials include circulating fluidized bed ash, cement, a conditioning agent and an activator; the activated alumina refers to an alumina component that can completely react with sufficient calcium oxide at 100° C. within 3 hours; The raw materials and the retarder are mixed to obtain the excited state admixture.

2. The method according to claim 1, characterized in that: The conditioning agent includes one or more of anhydrite, hemihydrate gypsum and dihydrate gypsum.

3. The method according to claim 1 or 2, characterized in that: The amount of the conditioning agent added is controlled by Formula I: (M1×AA1 CFB灰渣 +M2×AA1 激发剂 +M3×AA1 水泥 )×0.0098 / (0.0125S)>0.5 Formula I, In Formula I, AAl CFB灰渣 AAl is the mass percentage of activated alumina in circulating fluidized bed ash; 激发剂 is the mass percentage of activated alumina in the activator; AAl 水泥 is the mass percentage of activated alumina in cement, M1 is the mass percentage of circulating fluidized bed ash in excited admixture, M2 is the mass percentage of activator in excited admixture, M3 is the mass percentage of cement in excited admixture, and S is the mass percentage of total sulfur trioxide of circulating fluidized bed ash, cement, tempering agent and activator in excited admixture.

4. The method according to claim 1, characterized in that: The content of total sulfur trioxide in the excited state admixture is ≤7wt%.

5. The method according to claim 1, characterized in that The activator is a substance containing activated alumina.

6. The method according to claim 1 or 5, characterized in that: The activator comprises dye sludge containing activated alumina and / or sludge containing aluminum wastewater.

7. The method according to claim 1, characterized in that The mass percentage of the retarder in the excited state admixture is 0.01% to 0.5%.

8. The method according to claim 1 or 7, characterized in that: The retarder includes an organic retarder and / or an inorganic retarder; the organic retarder includes one or more of a carbohydrate compound, a carboxylic acid, a carboxylate, a polycarboxylic acid, a lignin sulfonate, a polyol and a polyol derivative; the inorganic retarder includes one or more of boric acid, a borate, a fluorine-containing silicate, a zinc salt, a barium salt and zinc oxide.

9. The method according to claim 7, characterized in that: The retarder also includes a water reducing agent.

10. The method according to claim 1, characterized in that The fluidity of the excited state admixture is 180±5 mm.